Surface Settlement Damage Model of Pile-Anchor Supporting Structure in Deep Excavation - Yuanxun Li; Wuyu Zhang; Ningshan Jiang; Hui Li (Advances in Civil Engineering)
In damage mechanics, the deep excavation of soil is a process of damage development, and soil failure can be considered a process of continuously transforming undisturbed soil to damaged soil. Therefore, this study considered the occurrence of soil damage during the pit excavation, established a soil damage model, damage evolution equation, and soil damage constitutive relationship, and then deduced a calculate model of the pile displacement under the consideration of soil damage. Based on the principle of the stratum loss method, the surface settlement around a deep excavated pit was assumed as a skewed distribution curve, and the surface settlement of the pile-anchor supporting pit was solved. Based on this established method, finite element analysis software was used to calculate the surface subsidence for a field case, and the numerical results were compared with monitoring data in the field. The results revealed that, to a certain extent, soil damage affected the distribution of surface settlement in excavated pits. With the development of soil damage, the mechanical properties of soil gradually decreased, which led to increased surface settlement and changes in the direction of the excavation pit. Because soil damage is an important factor causing surface settlement, it is meaningful to consider soil damage when calculating the surface settlement in the deep excavation of pits.